الإنتان في الداء المنجلي وإمكانية الوقاية - ميهوب, محمد; عثمان, منير; محمد, يحيى (Latakia University Journal -Medical Sciences Series, 2019)
أجريت دراستنا في قسم الأطفال في مشفى الأسد الجامعي في اللاذقية بهدف دراسة الإنتانات لدى مرضى الداء المنجلي وبحث إمكانية الوقاية منها. شملت الدراسة 68 مريضاً كان من بينهم 35 مريضاً مصاباً بالإنتان ، و21 مريضاً مصاباً بنوبة ألمية ، و21 مريضاً مصاباً بنوبة انحلالية. كانت ذات الرئة الإنتان الأشيع لدى مرضى الداء المنجلي ( 16 مريضاً ). قسمت مجموعة مرضى النوب الألمية بدون إنتان إلى مجموعتين: المجموعة (A) وضعت على خطة علاجية بدون صادات ، و المجموعة (B) وضعت على نفس الخطة العلاجية مع الصادات ، فوجدنا أنه لا دور للصادات في تقليل مدة استشفاء هؤلاء المرضى . أوصي جميع المرضى ببرنامج وقائي لتخفيف الإنتانات لديهم يتضمن لقاح المكورات الرئوية عديدة السكاريد، لقاح المكورات الرئوية المقترن، لقاح المكورات السحائية، لقاح المستدميات النزلية، البنسلين الفموي. Our study is carried out in the Department of Pediatrics at AL-ASSAD University Hospital in Lattakia to examine the infection in patients of sickle cell disease and the possibility of prevention. This study has included 68 patients, 35 of whom has had infections, 21 patients has had painful fits, and 12 patients has had hemolytic bout. Pneumonia is the common infection (16 patients). Patients of painful fits without infection are divided into two groups: patients of group A have undergone a therapeutic plan without antibiotics; patients of group B have received the same therapeutic plan plus antibiotics. We have concluded that antibiotics play no role in reducing hospitalization. Thus, we have advised patients to follow a prevention program, including pneumococcal polysaccharide vaccine, pneumococcal conjugate vaccine, meningococcal vaccine, haemophilus influenza type B vaccine, andoral penicillin, geared to reducing infections.